2000
DOI: 10.7326/0003-4819-132-8-200004180-00004
|View full text |Cite
|
Sign up to set email alerts
|

Invasive and Noninvasive Strategies for Management of Suspected Ventilator-Associated Pneumonia

Abstract: Compared with a noninvasive management strategy, an invasive management strategy was significantly associated with fewer deaths at 14 days, earlier attenuation of organ dysfunction, and less antibiotic use in patients suspected of having ventilator-associated pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
476
2
45

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 807 publications
(529 citation statements)
references
References 37 publications
6
476
2
45
Order By: Relevance
“…Our criteria for clinical suspicion of E-HAP are widely accepted. 12,13,16,18,24 Moreover, the retrospective calculation of the mCPIS allowed a positive confirmation of the diagnosis of pneumonia. 24 In unselected populations of mixed ICU patients, an incidence of early-onset pneumonia between 5% and 25% has usually been reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our criteria for clinical suspicion of E-HAP are widely accepted. 12,13,16,18,24 Moreover, the retrospective calculation of the mCPIS allowed a positive confirmation of the diagnosis of pneumonia. 24 In unselected populations of mixed ICU patients, an incidence of early-onset pneumonia between 5% and 25% has usually been reported.…”
Section: Discussionmentioning
confidence: 99%
“…12,[16][17][18] All chest radiographs were analyzed prospectively by 2 of the investigators (S.J. and C.P.-B.).…”
Section: Perioperative Managementmentioning
confidence: 99%
“…55 58 61 A much larger study involving 413 patients suspected of having VAP suggested that an invasive diagnostic strategy was desirable. 59 Compared with patients who received clinical management, patients who received invasive management had reduced mortality rate at day 14 (16.2% and 25.8%, p = 0.02) and decreased antibiotic use (mean (SD) number of antibiotic free days, 5.0 (5.1) and 2.2 (3.5), p,0.001). Most recently a meta-analysis of randomised, controlled trials of invasive diagnostic strategies in suspected VAP reported that an invasive approach did not change mortality (odds ratio 0.89, 95% confidence interval 0.56 to 1.41), but did change antibiotic use (odds ratio for change in antibiotic management after invasive sampling, 2.85, 95% confidence interval 1.45 to 5.59).…”
Section: Microbiological Diagnosismentioning
confidence: 99%
“…In a large, multicenter, randomized, unblinded French study of 413 critically ill patients with a clinical suspicion of pneumonia, bronchoscopy with quantitative cultures of PSB or BAL was compared to nonquantitative endotracheal aspirates (64). Patients with recent changes in antibiotic therapy were excluded, limiting the ability to generalize the results.…”
Section: Microbiologic Diagnosismentioning
confidence: 99%